(untitled) (Scientific journal of the Fergana State University, 2024)
In the context of globalization in education, given the fact that students learn about news through the media and social networks, it is advisable for a science teacher to regularly enrich the topic of his lesson with news. This article discusses the methodology for teaching the design and modeling of sewing materials, the role and significance of the science “Design and modeling of sewing materials”, the role in the development of special competence of future teachers of technological education.